The Influence of the Problem Based Learning Model on Ability Solution Problem Reviewed of students' Mathematical Self-Efficacy - Mahmud, Ramlan; Habbab, Aulidiyah; Kamaruddin, Rahmat (Indonesian Journal of Learning Education and Counseling, 2024)
This research is an experimental study that uses a Quasi Experimental approach which aims to describe the effect of the Problem Based Learning learning model on problem solving skills in terms of mathematical self-efficacy of MTs Nuhiyah Pambusuang. The population in this study were all seventh grades students of 2023/2024schools year , composed of 4 classes and the research sample were class VIIA with the Problem Based Learning model in pairs and VIID with the Problem Based Learning models in groups. Data collection techniques used pre-tests and post-tests to measure students ' problem solving abilities before and after applied the model and questionnaires related to students' self-efficacy. The data analysis techniques used ANAKOVA. The results of the study showed the Problem Based Learning model had an effect on students ' mathematical problem-solving skills as seen from the significant differences between pretest and posttest results and the gain in problem solving skills were in the medium category . However , the average gain value of problem-solving abilities of Problem Based Learning model in pairs is higher than the Problem Based Learning models in groups . In addition , Self-Efficacy had no effect on the problem-solving abilities of seventh grades of MTs Nuhiyah Pambusuang.